Associations of inflammatory cytokines with inflammatory bowel disease: a Mendelian randomization study - Song, Zhaoxiang; Li, Xiangyu; Xie, Jinlin; Han, Fei; Wang, Nan; Hou, Yuhan; Yao, Jianning (Frontiers in Immunology, 2024)
Objectives: This study employed the Mendelian randomization (MR) method to assess the causal relationship between 18 inflammatory cytokines and inflammatory bowel disease (IBD). Method: Two-sample Mendelian randomization utilized genetic variances associated with IBD from two extensive publicly available genome-wide association studies (GWAS) (Crohn’s Disease (CD): 12,194 cases and 28,072 controls; Ulcerative Colitis (UC): 12,336 cases and 33,609 controls) and inflammatory cytokine data from a GWAS summary comprising 8,293 healthy participants. Causalities between exposures and outcomes were primarily explored using the inverse variance weighted method. Additionally, to fortify the final outcomes, multiple sensitivity analyses, including MR-Egger, weighted median, simple mode, and weighted mode, were concurrently employed. Results: The findings indicated suggestive positive associations between Interleukin-13 (IL-13) and macrophage migration inhibitory factor (MIF) with Crohn’s Disease (CD) (odds ratio, OR: 1.101, 95%CI: 1.021-1.188, p = 0.013; OR: 1.134, 95%CI: 1.024-1.255, p = 0.015). IL-13 also exhibited a significant positive correlation with ulcerative colitis (UC) (OR: 1.099, 95%CI: 1.018-1.186, p = 0.016). Stem cell factor (SCF) was suggested to be associated with the development of both CD and UC (OR: 1.032, 95%CI: 0.973-1.058, p = 0.012; OR: 1.038, 95%CI: 1.005-1.072, p = 0.024). Conclusion: This study suggests that IL-13 might be a factor correlated with the etiology of IBD (CD and UC), while MIF might be specifically associated with CD. Additionally, SCF appears more likely to be involved in the downstream development of IBD (CD and UC).